Investor Perceptions of Financial Performance Announcements and Their Impact on Trading Decisions: A Phenomenological Study of Commodity Cycle Companies - Sandopart, Dewa Putu Yohanes Agata L. (Jurnal Ekonomi, Manajemen, dan Bisnis, 2024)
Theoretically, profit and loss announcements should serve as fundamental signals guiding investment decisions. However, empirical evidence suggests that investors, particularly those trading in commodity cycle companies, often make decisions that are not entirely rational. This study aims to explore in depth how investor perceptions of financial performance announcements are formed and how these perceptions influence trading decisions in commodity cycle companies. Employing a qualitative phenomenological approach, the research involved 18 informants, including retail investors, investment managers, and securities analysts actively trading shares of commodity companies on the Indonesia Stock Exchange. Data were collected through semi-structured interviews and participant observation in investor discussion forums and subsequently analyzed using interpretative phenomenological analysis. The main findings reveal four central themes: the ambiguity of profit meaning amidst commodity volatility, emotional heuristics as the primary mediator of perception, cognitive dissonance between fundamental information and actual trading behavior, and social proof within investor communities as a decision catalyst. This study contributes to the expansion of behavioral finance theory by demonstrating that investor perception operates through dual-processing mechanisms that diverge from perfect rationality assumptions. Practically, the findings underscore the need for financial literacy programs that account for the psychological aspects of commodity cycle investors.